WATER QUALITY MONITORING SYSTEM IN SHRIMP POND USING MICROCONTROLLER - al Imran Imran; Abdul Muis Mappalotteng; M. Arwan Setiawan (Jurnal Media Elektrik, 2024)
The study aimed to monitor air quality seen from the aspects of pH, temperature, and turbidity levels in shrimp ponds to increase the production of shrimp farmers. The study used Research and Development (R&D) method with a prototype development model. The subjects in this study were shrimp farmers in Pangkep Regency, South Sulawesi. It produced a prototype of an Internet Of Things (IoT)-based air quality monitoring tool that used a pH sensor, temperature sensor, turbidity sensor as an air quality detector. This product used an Esp32 microcontroller as a storage for air quality monitoring data and the Blynk application as a real-time information sender. The results of the functionality test showed that the tool was very feasible to use (100%) and the usability test by respondents showed that the tool developed was very good.